Heterogeneous tumor‐immune microenvironments between primary and metastatic carcinoid tumors differentially respond to anti‐PD‐L1 antibody therapy. Issue 3 (9th December 2020) - Sakata, Shinya; Imamura, Kosuke; Tajima, Yuka; Masuda, Yuiko; Sato, Ryo; Yoshida, Chieko; Okamoto, Shinichiro; Saeki, Sho; Tomita, Yusuke; Sakagami, Takuro
Abstract : A pulmonary carcinoid tumor is a rare tumor that lacks a validated therapeutic approach for unresectable disease. Understanding the intersite tumor‐immune heterogeneity is essential to harness the immune system for cancer therapy. However, little is known about the tumor‐immune microenvironment (TIME). Here, we describe a patient who had heterogeneous TIME between primary and metastatic carcinoid tumors which differentially responded to chemoimmunotherapy. A 72‐year‐old man was diagnosed with an advanced pulmonary carcinoid tumor. CT‐guided biopsies of lung and scapular tumors confirmed typical carcinoid (PD‐L1, 1%–24%) and atypical carcinoid tumors (PD‐L1, negative), respectively. Although the primary lung carcinoid tumor showed a partial response, the scapular tumor was significantly enlarged after two cycles of anti‐PD‐L1 antibody therapy in combination with carboplatin plus etoposide. We performed quantitative pathology imaging analysis with fluorescent multiplex immunohistochemistry. CD8 + T cell infiltration was detected in the PD‐L1‐positive primary lung tumor nest; however, it was mostly restrained in the stroma in a PD‐L1‐negative metastatic scapular tumor. Treg infiltrations into both tumor nests and stroma were detected in the lung tumor, which were not detected in the metastatic scapular tumor. This study provides the first evidence of coexistence of heterogeneous TIME within a single individual with a pulmonary carcinoid tumor. This study may provide new insights into the mechanism of primary resistance to chemoimmunotherapy in pulmonary carcinoid tumors. Abstract : We describe a patient who had heterogeneous TIME between primary and metastatic carcinoid tumors which differentially responded to chemoimmunotherapy. CD8+ T cell infiltration was detected in PD‐L1‐positive primary lung tumor nest, however, which was mostly restrained in the stroma in a PD‐L1‐negative metastatic scapular tumor. This study may provide new insights into the mechanism of primary resistance to chemoimmunotherapy in pulmonary carcinoid tumors.